Samiska kvinnors levnadsvillkor i kulturen och rennäringen - Nilsson, Gunilla (Högskolan Väst, Avd för psykologi och organisationsstudier, 2009)
Previous research often includes juridical, political, economical and historical aspects of the Sami population. The research about the Sami women are limited therefore is was important to investigate the living conditions of the Sami women. The purpose with the study was to investigate the living conditions of the Sami women from a culture- and reindeer-herding view in relation to social gender and the majority society. Four individual interviews were performed with women who worked with reindeer-herding in the Sapmi area in north of Sweden. The interview guide was semi-structured and the data were analysed with the phenomenological method Interpretative Phenomenological Analysis, which has a focus on subjective experiences. The results revealed that participants try to create a norm of practising reindeer-herding, in spite of the male norm and less physical strength. They experience that job sharing between genders has changed over time. The majority society was experienced as threatening due to diffused intentions for reindeerherding. Mycket litteratur behandlar samerna ur juridiskt, politiskt, ekonomiskt och historiskt perspektiv. Forskningen om samiska kvinnor är begränsad och därför är det angeläget att undersöka samiska kvinnors levnadsvillkor. Syftet med denna studie var att studera samiska kvinnors levnadsvillkor i rennäringen i förhållande till socialt kön och majoritetssamhället. Fyra kvinnor som arbetar helt eller delvis med renskötsel intervjuades. Intervjuerna har varit semi-strukturerade och har utförts i norra Sápmi. Data analyserades med den fenomenologiska metoden Interpretative phenomenological analysis, som fokuserar på människors upplevelser av fenomen. Tvärtemot normen så visar resultatet att kvinnorna själva kan göra det möjligt att klara av att anta renskötarrollen, trots fysiska hinder, maskulinisering och strukturer. Renskötseln är uppbyggd som en manlig struktur och arbetsdelning har omvandlats under olika tider. Majoritetssamhället upplevdes som ett hot eftersom informanterna kände ...